A Mutual Awareness Mechanism of Inter-MVFs (Mobile Virtual Fences) to Support Connected Car Service - Kim, Inhwan; Yoo, Hyunmi; Young-Hyun, Eom; Cho, Sungguk; Jeon, Byungkook (International Journal of Engineering and Technology, 2018)
In this paper, we present a mutual awareness mechanism among lots of MVFs(Mobile Virtual Fences) to configure Connected cars service in VANETs(Vehicular Ad hoc Networks). If the MVFs, as our previous researches, mounted on each car are recognized and constructed to each other, the service environment of connected car can be configured and simulated. So it is necessary to have a mechanism that the moving MVFs automatically detect according to the speed. The proposed mutual awareness mechanism is implemented by exchanging messages among inter-MVFs based on context-aware computing. As a result, when the MVFs are mutually recognized, they are basically simulated in a connected car service. Therefore, in the future, the proposed mechanism will be contribute to improve the reliability, safety, and efficiency in the era of autonomous vehicles.Â Â